Strategi Komunikasi KONI Sumatera Utara Pada Pelatda Atlet Pekan Olahraga Nasional (PON) Ke-XX Papua - Agung Sunarno; Augina Amelia Putri (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2022)
used by the Indonesian National Sports Committee of North Sumatra Province in carrying out the regional training center for athletes at the XXI National Sports Week in Papua in 2021. The research method used was a qualitative descriptive method. 6 People consist of 4 components in Pelatda activities, namely the Head of Pelatda, Wasping, Trainers, and Athletes, using a purposive sampling technique. Data collection techniques using interviews, observation, and documentation techniques. Data analysis techniques were carried out through data reduction, data presentation, and concluding. The results of this study show that the communication strategy used by KONI North Sumatra is very good, so it has a very important role in creating outstanding athletes in PON activities. The communication strategy used is to communicate directly to create closeness and establish good communication between all components of Pelatda.